Differentiation of Real Estate in an International Context (Economic journal of Lesya Ukrainka Volyn National University, 2016)
This article revealed the essence of the concept of «property». Investigated value of real estate. The essence of real estate as a separate economic category, during which the disclosed dual nature of its operation, emphasizing its importance and greatly expands the scope of the study. Considered legislative and regulatory documents in Ukraine which disclosed the concept of «immovable». Exposed and systematic approach to the definition of real estate around the world with regard to the legal provision in the regulation of private relations. The study highlights the main features of immovable and determined its physical, economic, social and legal characteristics. Determined lack of communication on integrated management of international real estate market. Specifies that the regulation of the real estate market is separately in each country within its legal system.
Keywords: real estate, fixed thing, property, real estate, real estate market, local real estate market, real estate in the region